2016
DOI: 10.1007/s00330-016-4420-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visibility of circumscribed masses on Digital Breast Tomosynthesis (DBT) and 2D mammography: are circumscribed masses better visualized and assured of being benign on DBT?

Abstract: • Circumscribed masses were better visualized on breast tomosynthesis than on 2D mammography. • Tomosynthesis visualized circumscribed masses better than 2D for all breast density categories. • Halo signs often appeared on tomosynthesis and contributed to detect circumscribed margins. • Circumscribed masses on tomosynthesis images are not assured of being benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Although DBT has better diagnostic performance than DM, still some breast lesions could not be determined on DBT. On DBT images, improved visualization of a partially or totally smooth boundary in some malignant masses may potentially lead to a misdiagnosis that is false benign diagnosis [29]. Thirty-six of the breast lesions in this study were misdiagnosed on DBT (20 false-positives and 16 falsenegatives).…”
Section: Discussionmentioning
confidence: 81%
“…Although DBT has better diagnostic performance than DM, still some breast lesions could not be determined on DBT. On DBT images, improved visualization of a partially or totally smooth boundary in some malignant masses may potentially lead to a misdiagnosis that is false benign diagnosis [29]. Thirty-six of the breast lesions in this study were misdiagnosed on DBT (20 false-positives and 16 falsenegatives).…”
Section: Discussionmentioning
confidence: 81%
“…A feature to keep in mind when analysing the contour of nodular lesions is the halo sign, defined as a thin hyperlucent ring that surrounds >50% of the margin of the nodule and is detected BJR Full paper: Halo sign in young women with synthesized 2D mammography in at least one mammographic view. 7 On the other hand, the mechanism and significance of the halo sign have changed in line with the development of mammography systems. Wolfe 9 suggested that the halo sign results from the compression of fat by the circumscribing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…They used an optical magnification method (magnifying glass or binocular microscope) and suggested that a halo is not always a perceptual illusion seen around benign and malignant lesions. Nakashima et al 7 suspected that halo signs in digital mammography are magnified due to the contour highlight effect of image processing. Furthermore, in tomosynthesis, this contour highlight effect overlaps due to the reconstruction of a limited number of data samples with a narrow angular range of X-ray emissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations